1999
DOI: 10.1590/s1516-35981999000100007
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças genéticas e estimação de coeficientes de herdabilidade para características morfológicas em fêmeas zebus e F1 holandês x zebu

Abstract: O objetivo deste trabalho foi averiguar possíveis variações nas mensurações morfológicas entre reprodutrizes zebus dos grupos genéticos (GG) Indubrasil, Nelore e Tabapuã e entre os GG de suas filhas F1 Holandês x Indubrasil (HxI), Holandês x Nelore (HxN) e Holandês x Tabapuã (HxT), além de estimar coeficientes de herdabilidade (h²) para estas características. O método dos quadrados mínimos foi usado para verificação das diferenças nas características morfológicas entre os GG e para obtenção de estimativas de h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…The heritability estimates for T of 0.18 6 0.02 (Table 3) was similar to those reported by Mishra et al (1975), Mourã o et al (1998) and Phocas et al (2006), but were lower than those observed by Burrow (2001) for animals of tropical breeds (0.40 to 0.44). Nevertheless, the magnitude of the estimate obtained in this study, together with the low magnitude of its respective standard error, which confers reliability, suggests that temperament presents sufficient additive genetic variability in the Nellore breed to respond to selection.…”
Section: Discussionsupporting
confidence: 88%
“…The heritability estimates for T of 0.18 6 0.02 (Table 3) was similar to those reported by Mishra et al (1975), Mourã o et al (1998) and Phocas et al (2006), but were lower than those observed by Burrow (2001) for animals of tropical breeds (0.40 to 0.44). Nevertheless, the magnitude of the estimate obtained in this study, together with the low magnitude of its respective standard error, which confers reliability, suggests that temperament presents sufficient additive genetic variability in the Nellore breed to respond to selection.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the sexual performance of males was evaluated, as shown in Table 1. To assess temperament, the vanishing point was used as a scoring parameter (adapted from MOURÃO et al, 1999). The rating scale used is from 1 to 6 points, with 1 being extremely reactive animals and 6 being extremely tame animals.…”
Section: Methodsmentioning
confidence: 99%
“…A literatura demonstra que animais mais dóceis crescem melhor que animais ariscos (Tulloh, 1961;Voisinet et al, 1997) e que o estresse tem efeito deletério sobre os caracteres de qualidade de carne (Grandin, 1980;Fordyce et al, 1988), o que demonstra a necessidade de se selecionar animais de temperamento mais dócil. O temperamento em bovinos é uma característica herdável, apresentando uma herdabilidade moderada, entre 0,25 e 0,50 (Le Neindre et al, 1995;Mourão et al, 1998;Silva et al, 2003). Desta forma, o temperamento se apresenta como um caráter que pode ser incluído em programas de melhoramento genético, com objetivo de selecionar animais menos reativos.…”
Section: Introductionunclassified